Dissecting aneurysm of the interventricular septum due to rupture of the sinus of Valsalva. (22nd November 2016) - Atiq, Mehnaz; Ali, Fatima; Hasan, Sulaiman B.
Abstract: Aneurysm of the sinus of Valsalva is a rare congenital cardiac anomaly. It occurs as an outpouching that progresses like a windsock, and it may rupture producing aortic regurgitation, cardiac tamponade, congestive heart failure, conduction abnormalities, and stroke. We describe a case of rupture of the sinus of Valsalva into the interventricular septum producing a large dissecting aneurysm. Despite the location, it did not produce a conduction abnormality.